High-Fat Diet Alters the Expression of Reference Genes in Male Mice - Fan, Xiuqin; Yao, Hongyang; Liu, Xuanyi; Shi, Qiaoyu; Lv, Liang; Li, Ping; Wang, Rui; Tang, Tiantian; Qi, Kemin (Frontiers in Nutrition, 2020)
The quantitative PCR (qPCR), the most accurate and sensitive technique for quantifying mRNA expression, and choice of appropriate reference genes for internal error controlling in qPCR, are essential to understand the molecular mechanisms that drive obesity epidemic and its comorbidities. In this study, using the high-fat diet (HFD) induced obese mouse model, we assessed the expression of 10 commonly used reference genes to validate gene-expression stability in adipose tissue, liver and muscle across different time points (4, 8, 12 and 16 weeks after HFD feeding) during the process of obesity. The data were analyzed by the GeNorm, NormFinder, BestKeeper and Delta-Ct methods, and the results showed that the most stable reference genes were different for a specific organ or tissue in a specific time point, however, PPIA, RPLP0 and YWHAZ were the top three most stable reference genes in qPCR experiments on adipose, hepatic tissues, and muscles of mice in diet-induced obesity. In addition, the mostly used genes ACTB and GAPDH were more unstable in the fat and liver, the ACTB mRNA levels were increased in four adipose tissues and the GAPDH mRNA levels were decreased in four adipose tissues and liver after HFD feeding. These results suggest that PPIA, RPLP0 or YWHAZ may be more appropriate to be used as reference gene than ACTB and GAPDH in the adipose tissue and liver of mice during the process of high-fat diet-induced obesity.